Cerebral Fat Embolism That Was Initially Negative on DiffusionWeighted Magnetic Resonance Imaging - Seung Je Go; Yun Su Mun; Seung Ho Bang; Yong Han Cha; Young Hoon Sul; Jin Bong Ye; Jae Guk Kim (Journal of Trauma and Injury, 2021)
Fat embolism syndrome is a rare, but serious condition that occurs in patients with fractures of the long bones or who undergo orthopedic surgery. The main clinical features of fat embolism syndrome are an altered mental status, hypoxia, and petechial rash. Cerebral fat embolism is the most severe manifestation of fat embolism syndrome because it can lead to an altered mental status. The diagnosis of cerebral fat embolism is clinical, but brain magnetic resonance image (MRI) is helpful. There is usually an interval until symptoms, such as an altered mental status, develop after trauma. We report a case of cerebral fat embolism in which the patient’s mental status deteriorated several hours after trauma and the initial findings were negative on diffusion-weighted MRI.